Fascia Lata Harvesting: The Donor Site Closure Morbidity. Issue 4 (June 2019) - Giovannetti, Filippo; Barbera, Giorgio; Priore, Paolo; Pucci, Resi; Della Monaca, Marco; Valentini, Valentino
Abstract : Objective: Fascia lata (FL) is a worldwide adopted source of autologous grafts. In our Department, the endoscopic endonasal transphenoidal surgery (EETS) has been performed regularly for anterior and middle cranial fossa lesions, and FL graft has commonly been a practical resource in repairing tissue defects after EETS. Enough, we used routinely harvesting FL to restore symmetry in facial palsy. To our known, this is the biggest case series about FL harvesting to repare tissue defects after EET. The purpose of our study was to evaluate our experience with the harvesting of FL, in particularly the donor site morbidity. Study design: This is a prospective study case series, which evaluated by questionnaire the morbidity of FL donr site. Methods: The details of 44 patients were analyzed from 2011 to 2016. Thirty-eight patients needed cranial base reconstruction and 6 patients needed facial reanimation. Results: Adequate length of FL was harvested in all our patients. There were no intraoperative complications. We did not use drain in any case. We analyzed 18 women (40%) and 26 men (59.9%). The estimated median age at presentation was 51.53. Conclusion: For little FL's gap, diameter until 3 × 6 cm, it's possible to suture FL's margin with Nylon, but for bigger gap it's necessary to reconstruct with allograft to avoid muscle bulge or compartmental syndrome.